Shiny misfits - Zayid, Maysoon (Graphix, an imprint of Scholastic, 2024)
Bay Ann is sure her tap dance will shine at the school talent show, but when her crush, Alyee Maq, catches her before she falls (which was his fault anyway) and gets all the "fame" she is determined to beat him at his own attention-seeking game.